La publicité au service de la dissimulation - Héloïse Hermant (Mélanges de la Casa de Velázquez)
Through the two wars of words orchestrated by don Juan José de Austria against the validos of the regent Mariana in 1668-1669 and 1676-1677, this article analyses the way in which Philip IV’s bastard son placed publicity at the service of dissimulation in order to secure the dismissal of his political enemies and have himself appointed Vicar-General of Aragon in 1669 and First Minister in 1677. Having undermined any accusation of rebellion by building a reputation as a defender of the common weal, don Juan stretched the rules of political negotiation with the authorities, being as he was in a position to resist without open disobedience. His action, viewed by some as Machiavellian and by some as Christian prudence, constitutes a model example of grandeza in the face of crisis. This model justifies the central role of the nobility in the monarchy and enshrines reason as the wellspring of political action.